(untitled) (ENTHYMEMA, 2020)
This paper analyses verses 49-141 «Inferno»’s twenty-sixth canto of Dante’s Divine comedy. It is studied from Roland Barthes’ understanding of mythology, as opposed to the classic conception that the myth is a narration. This analysis is useful to observe how Dante manipulates some pagan characters, especially Ulysses, to make them fit in a Christian context.